Rhizosphere Soil Microbial Community Under Ice in a High-Latitude Wetland: Different Community Assembly Processes Shape Patterns of Rare and Abundant Microbes - Ma, Jiaming; Ma, Kang; Liu, Jingling; Chen, Nannan (Frontiers in Microbiology, 2022)
The rhizosphere soil microbial community under ice exhibits higher diversity and community turnover in the ice-covered stage. The mechanisms by which community assembly processes shape those patterns were poorly understood in high-latitude wetlands. Based on the 16S rRNA gene and ITS sequencing data, we determined the diversity patterns for the rhizosphere microbial community of two plant species in a seasonally ice-covered wetland, including during the ice-covered and ice-free stages. Ecological processes of community assembly were inferred by the null model at phylogenetic bins (taxonomic groups divided according to phylogenetic relationships) level. Different effects of ecological processes on rare and abundant microbial subcommunities (defined by the relative abundance of bins) and bins were further analyzed. We found that bacterial and fungal communities had higher alpha and gamma diversity under the ice. During the ice-free stage, the dissimilarity of fungal communities decreased sharply and?the spatial variation disappeared. For the bacterial community, homogeneous selection, dispersal limitation, and ecological processes (undominated processes) were the main processes, and they remained relatively stable across all stages. For the fungal community, during the ice-covered stage, dispersal limitation was the dominant process, while during the ice-free stage, ecological drift processes were more important in the Scirpus rhizosphere, and ecological drift and homogeneous selection processes were more important in the Phragmites rhizosphere. With regards to the different effects of community assembly processes on abundant and rare microbes, abundant microbes were controlled more by homogeneous selection, rare microbes were more controlled by ecological drift, dispersal limitation, and heterogeneous selection, especially for bacteria. This is potentially caused by the low growth rates or the intermediate niche breadths of rare microbes under the ice. Our findings suggest the high diversity of fungal communities under the ice, deepen understanding of various ecological processes of community assembly across stages, and reveal the distinct effects of community assembly processes on abundant and rare microbes at the bins level.